Strategy for Constructing Religious Authority in the Digital Pulpit: Study of Three Indonesian Preachers on YouTube - Pranoto, Stepanus Sigit (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
This article discusses the strategies of three YouTube Indonesian Islamic preachers in constructing their religious authority in the digital pulpit. YouTube accommodates Islamic preachers to produce da’wah content that is accessible to the wider community. In this case, these Islamic preachers not only convey various Islamic information and knowledge, but also seek to construct religious authority in the digital public sphere. The three Islamic preachers examined in this study are Ustadz Steven Indra Wibowo, KH Abdul Syakur Yasin and Habib Husein Ja’far Al Hadar. They have different backgrounds and characters. Using mediatization approach and netnography method to examine the da’wah content on the YouTube channels of the three Islamic preachers, this study concludes there are three kinds of strategies they used in constructing authority, namely 1) identity commodification strategy, 2) network collaboration strategy, and 3) interactive communication strategy. These three kinds of strategies become supporting factors for the preachers in constructing their Islamic authority through the YouTube platform.